Religion and justice - Vinayaraj, Y.T. (Bangalore, CISRS, 2022)
This book is a rich, well-documented resource drawn from the discussion forums of the Christian Institute for the Study of Religion and Society (CISRS), which is regarded as an avant-garde movement for the renewal of religion and society in this country. The practice of religion by individuals and groups, the context of religious diversity, and the fear of religious extremism, raise serious concerns about the interaction between religion and justice in society.
Contributed articles on Religion and justice
Keywords: Religion; Religion and Social Justice; Religion and Society; Contributed articles